1969
DOI: 10.12669/pjms.306.5541
|View full text |Cite
|
Sign up to set email alerts
|

Type A and Type B Personality in Undergraduate Medical Student: Need of Psychosocial Rehabilitation

Abstract: Objectives: To find out the frequency of Type A and Type B personality among the students of Undergraduate Medical College. To find association between student year and personality type. Methods: A descriptive cross sectional study was conducted at Undergraduate Medical College, Rawalpindi from Sept. 2012 till Feb. 2013. Among 500 sample size, 100 students from each MBBS year were inducted by probability systematic sampling technique. After taking consent from the institute and students, data was collected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…TABP has been identified as a predisposing factor to both increased stress and a maladaptive coping response to stress [ 47 , 104 ]. TABP has been found in11% of medical students [ 38 ] compared to 26% in university students [ 39 ]. The prevalence of TABP in the present sample was approximately 12% among female students without acne and 24% in the AV sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TABP has been identified as a predisposing factor to both increased stress and a maladaptive coping response to stress [ 47 , 104 ]. TABP has been found in11% of medical students [ 38 ] compared to 26% in university students [ 39 ]. The prevalence of TABP in the present sample was approximately 12% among female students without acne and 24% in the AV sample.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas [ 37 ] showed that Type B individuals experience less stress due to daily frustration, feel less pressured by too many tasks to complete, enjoy their life more, are more satisfied with their work, and have better general health than Type A people. Hisam et al [ 38 ] found a rate of TABP of approximately 11% among a large sample of medical students ( n = 500). Among Romanian university students, a high-stress level (44% of the sample), alexithymia (26%), and Type A (26%) and Type C (17%) personality patterns are much more prevalent compared to the general population, especially in medical students [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the some studies, type A behaviour and personality pattern are defined as a type of behaviour presented by individuals who are highly competitive, success oriented, always in a hurry, impatient, easily excited, as well as those with fast talking and explosive speech. There is a significant proportion of scientific evidence that demonstrated a correlation between type A behaviour and development of cardiovascular diseases [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Type A is a behavior pattern characterized by impatience, time urgency, hostility, and aggressiveness. It has been reported to be associated with coronary artery disease since the 1950s [24].…”
Section: ) Personalitymentioning
confidence: 99%